EARLY ACTIVATION OF SPLENIC MACROPHAGES BY TUMOR-NECROSIS-FACTOR-ALPHA IS IMPORTANT IN DETERMINING THE OUTCOME OF EXPERIMENTAL HISTOPLASMOSIS IN MICE - Wuhsieh, B. A.; Lee, G. S.; Franco, M.; Hofman, F. M. (Amer Soc Microbiology, 1992)
Experimental infection of animals with Histoplasma capsulatum caused a massive macrophage infiltration into the spleen and induced the production of tumor necrosis factor alpha (TNF-alpha) locally. The cytokine was also produced in vitro by peritoneal exudate macrophages exposed to a large inoculum of yeast cells. Depletion of the cytokine by injection of polyclonal sheep anti-TNF-alpha antibody was detrimental to sublethally infected mice. Fungous burdens in the spleens of TNF-alpha-depleted mice were higher than they were in the infected control mice at days 2, 7, and 9 after infection, and the antibody-treated animals succumbed to the infection. Histopathological study of spleen sections revealed that splenic macrophages were not able to control proliferation of intracellular yeasts as a result of TNF-alpha depletion. It seems that TNF-alpha plays a role in early activation of splenic macrophages which is important in controlling the outcome of an infection.